Relationship of chronic endometritis with chronic deciduitis in cases of miscarriage - Shoji Kaku; Takuro Kubo; Fuminori Kimura; Akiko Nakamura; Jun Kitazawa; Aina Morimune; Akimasa Takahashi; Akie Takebayashi; Akiko Takashima; Ryoji Kushima; Takashi Murakami (BMC, 2020)
Abstract Background The presence of chronic deciduitis (CD) was determined in patients diagnosed with or without chronic endometritis (CE) before pregnancy. Objective To study the effect of CE on decidua in cases of miscarriage. Methods Decidual tissue was obtained from the patients who miscarried at the first pregnancy within a year after the diagnosis of the presence or absence of CE. The number and distribution pattern of plasma cells stained with CD138 in decidual tissue in 10 high-power fields (HPFs) was examined. The prevalence of CD diagnosed with four different grade; grade 0, no plasma cell in 10 HPFs, thus Non-CD;grade 1, rare single plasma cells; grade 2, rare clusters or more than 5 single cells total; and grade 3, many plasma cells with more than 5 clusters, were examined and compared between Non-CE and CE. Results The incidence rate of CD of grade2 + 3 was significantly higher in CE than Non-CE (53.8%; 7/13 vs. 0%; 0/13, P < 0.01). Presence of clusters or a number of plasma cells in 10 HPFs of decidua showed a sensitivity of 53.8%, a specificity of 100%, a positive predictive value of 100%, and a negative predictive value of 68.4% for the diagnosis of CE. Conclusion Presence of clusters of plasma cells or five or more of plasma cells in decidua was found in more than half of CE, but not found in Non-CE. When CD with cluster or five or more of plasma cells is confirmed histologically in miscarriage decidual tissue, the presence of CE before the pregnancy should be suspected.